P57MicroRNA-150 activates expression of MAP2K4 during hypoxia/reoxygenation in cardiomyocytes. (15th July 2014) - Yeh, CH; Chen, TP; Wang, YC; Chien, HJ; Liang, HY; Fang, SW; Fang, YC
Abstract: Purpose: MicroRNAs (miRNAs), which are regulators of gene repression and steimulation, participate in diverse biological functions in association with ribonucleoprotein factors and cellular conditions. Methods: In this study, we show that microRNA-150 (miR-150) is significantly up-regulated in hearts under hypoxia/reperfusion injury. Persistent expression of miR-150 in H9c2 cells significantly increased in vitro cellular porliferation as well as ameliorated hypoxia/reoxygenation-induced cellular injury. We used a computational approach and identified three hundred and eighteen miR-150 candidate target genes from three independent expression microarray datasets. Results: Sixteen target genes were empirically verified, and this group of genes was enriched with genes regulating hypertrophic cardiomyopathy, dilated cardiomyopathy, calcium signaling, focal adhesion, and transcription. We further showed that one of the miR-150 targets, MAP2K4 is involved in cellular survival. Silencing of miR-150-transfected H9c2 stable clone with antagomir during hypoxia/reperfusion injury resulted in a dramatic reduction of in vitro expression of MAP2K4 in a dose-dependent response, as well as increase the insult on H9c2 cells by way of p38MAPK/JNKs pathway. Conclusion: Our study suggests that miR-150, a cell survival microRNA enhances cardiomyocytic resistance to hypoxia/reoxygenation injury, exerts some of its action via activation of MAP2K4 and downstream p38MAPK/JNKs pathway. Persistent expression of miR-150 can rescue the cell from hypoxia/reoxygenation injury and increase the cardiomyocytic proliferation. Using the concomitant up-regulation of its targets, including MAP2K4, a rational therapeutic strategy based on miR-150 may prove to be beneficial for patients with cardiac ischemic/reperfusion insults.